1990
DOI: 10.1073/pnas.87.24.10063
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of delta 9-tetrahydrocannabinol to stimulate somatostatin release and block that of luteinizing hormone-releasing hormone by suppression of the release of prostaglandin E2.

Abstract: Physiology/PharmacologyIn vitro effect of A9-tetrahydrocannabinol to stimulate somatostatin release and block that of luteinizing hormone-releasing hormone by suppression of the release of prostaglandin E2 (in vitro 2). The central site of action of THC is also supported by the finding that in vivo administration of THC elevated the LHRH content in the mediobasal hypothalamus (MBH) (1, 3) at a time when plasma LH levels were lowered. It is known that the release of LHRH is stimulated by noradrenergic termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…ICV administration of THC elevated LHRH content in the MBH within 30 min followed by a decrease at 60 min, concurrent with lowered plasma LH levels in male rats (53). In vitro studies indicated that the suppressive effect of THC on LH release was because of the reduction in noradrenergic stimulation of prostaglandin E 2 (PGE 2 ) and LHRH release in MBH (54). De Miguel et al (42) have provided evidence for a role of CB 1 receptors in the suppressive effects of THC on LH release.…”
Section: Discussionmentioning
confidence: 99%
“…ICV administration of THC elevated LHRH content in the MBH within 30 min followed by a decrease at 60 min, concurrent with lowered plasma LH levels in male rats (53). In vitro studies indicated that the suppressive effect of THC on LH release was because of the reduction in noradrenergic stimulation of prostaglandin E 2 (PGE 2 ) and LHRH release in MBH (54). De Miguel et al (42) have provided evidence for a role of CB 1 receptors in the suppressive effects of THC on LH release.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous administration of cannabinoids influences neuroendocrine axes, e.g., it stimulates the hypothalamic-pituitary-adrenal (HPA) axis through CB1 (Murphy et al, 1998) and inhibits the hypothalamicpituitary-thyroid, gonadal, and growth hormone axes (Lomax, 1970;Tyrey, 1978;Rettori et al, 1990;Pagotto et al, 2006). In addition, the endocannabinoid system also plays a critical role in the hypothalamic control of energy homeostasis (Pagotto et al, 2006).…”
mentioning
confidence: 99%
“…Rettori et al [32] found in their study a reduced secretion of the growth hormone, both from the normal pituitary gland of man, as well as from cells of somatotropic adenomas, as an effect of cannabinoid activity, which the authors associated with stimulation of somatostatin release in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%